Tubulin Acetylation Mediates Bisphenol A Effects on the Microtubule Arrays of Allium cepa and Triticum turgidum - Adamakis, Ioannis-Dimosthenis S. (Biomolecules, 2019)
The effects of bisphenol A (BPA), a prevalent endocrine disruptor, on both interphase and mitotic microtubule array organization was examined by immunofluorescence microscopy in meristematic root cells of Triticum turgidum (durum wheat) and Allium cepa (onion). In interphase cells of A. cepa, BPA treatment resulted in substitution of cortical microtubules by annular/spiral tubulin structures, while in T. turgidum BPA induced cortical microtubule fragmentation. Immunolocalization of acetylated α-tubulin revealed that cortical microtubules of T. turgidum were highly acetylated, unlike those of A. cepa. In addition, elevation of tubulin acetylation by trichostatin A in A. cepa resulted in microtubule disruption similar to that observed in T. turgidum. BPA also disrupted all mitotic microtubule arrays in both species. It is also worth noting that mitotic microtubule arrays were acetylated in both plants. As assessed by BPA removal, its effects are reversible. Furthermore, taxol-stabilized microtubules were resistant to BPA, while recovery from oryzalin treatment in BPA solution resulted in the formation of ring-like tubulin conformations. Overall, these findings indicate the following: (1) BPA affects plant mitosis/cytokinesis by disrupting microtubule organization. (2) Microtubule disassembly probably results from impairment of free tubulin subunit polymerization. (3) The differences in cortical microtubule responses to BPA among the species studied are correlated to the degree of tubulin acetylation.